Cangkrukan an Adult Learning Model in Strengthening The Role of Pokdarwis in Surowiti Hill Tourism Village, Gresik, East Java - Roesminingsih, MV; Nugroho, Rivo; Rosyanafi, Rofik Jalal; Siswanto, Heru; Mardiani, Desika; Dewangga, Teguh (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
This research aims to describe the meaning of Cangkrukan as an adult learning model in strengthening the role of Pokdarwis in the Bukit Surowiti, Gresik tourist village, East Java. This research uses a qualitative approach with a case study method. The location of this research is Surowiti Village, Panceng District, Gresik, East Java. The informants in this study were Pokdarwis members, village officials, and local village community leaders. Data was collected by involving observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman interactive model. The research results show that the wheel government and Pokdarwis use dialogue media, social media, WhatsApp, and Cangkrukan in village tourism. Through Cangkrukan, the village government and Pokdarwis can convey the idea of a tourist village and get a direct response from the community. Cangkrukan can determine strategies to advance the community's tourism awareness through informal conversations. Cangkrukan can be an example of a community empowerment strategy based on local wisdom.